Nutrient, phytochemical, and digestibility evaluation of papaya leaves (Carica papaya L.) as an alternative feedstuff for ruminants - Muhamad Ichsan Haris; Hamdi Mayulu; Suyadi Suyadi (Faculty of Animal Science, Universitas Brawijaya, 2022)
Ruminants have a complex digestive system so they can utilize forage nutrients to convert them into food products of high economic value (meat and milk) and papaya leaves have the potential to be an alternative source of new feedstuff. The research was conducted at the Laboratory of Animal Feed Chemistry, Faculty of Animal Husbandry, Hasanuddin University Makassar (for proximate analysis), Laboratory of Animal Nutrition and Feed, Faculty of Animal Husbandry, Gadjah Mada University, Yogyakarta (for quantitative and qualitative analysis). The study was used proximate analysis to determine the nutritional content of papaya leaf, in vitro analysis to measure dry matter digestibility (DMD) and organic matter digestibility (OMD), and Thin-Layer Chromatography (TLC) for quantitative and qualitative tests of alkaloid compounds. The results showed that the DMD values of dry leaf and fresh leaf DMD were 72.74% and 78.44%, respectively. The highest score of rations DMD and OMD was R2FPL (69.98%) and R2DPL (61.92%), respectively. A qualitative test of papaya leaf bioactive compounds using UV 254 light obtained 3 spots with a detectable Rf value of 0.72 and a quantitative test with piperine test parameters showed the results of the analysis were